STRATEGIC PROCUREMENT PRACTICES AND ORGANIZATIONAL PERFORMANCE: A STUDY OF MANUFACTURING FIRMS IN LAGOS STATE, NIGERIA - John Edewor Oputa (Universitas Nurul Jadid, 2024)
The Nigerian manufacturing sector faces structural and operational challenges due to recent macroeconomic reforms, including petroleum subsidy removal, foreign exchange rate unification, and minimum wage increase, leading to cost-push inflation, reduced consumer purchasing power, and increased competition. This study investigates the impact of strategic procurement practices on the performance of manufacturing firms in Nigeria. Employing a mixed-method research design, the study integrates both quantitative and qualitative approaches to leverage their respective strengths. A sample size of 250 respondents was determined using Taro Yamane's formula, and purposive sampling techniques were employed to select participants from ten manufacturing companies situated in Ilupeju and Ogba Industrial Estates, Lagos State. Data were collected using structured questionnaires and analyzed through descriptive statistics and regression modelling to assess the relationship between strategic procurement practices and manufacturing firm performance. The findings reveal that for every unit increase in strategic procurement practices, the performance of manufacturing firms improves by 0.168 units, underscoring the significant role of strategic procurement in enhancing operational efficiency, cost reduction, product quality, competitiveness, and profitability. The study recommends that manufacturing firms adopt advanced strategic procurement practices, including e-procurement, e-sourcing, e-auctions, advanced analytics, predictive technologies, and blockchain systems to monitor market trends effectively. Furthermore, firms should implement agile procurement strategies and reverse logistics systems to facilitate cost recovery through the return, reuse, and recycling of materials and products.